Composite negative electrode material, negative electrode, preparation method of negative electrode, battery and electric equipment
By covering the prefabricated film on the negative electrode material of the lithium battery and dispersing the conductive agent therein, the mechanical design challenges and electrode internal resistance problems caused by the volume change of the negative electrode material are solved, and longer battery cycle life and higher electrochemical performance are achieved.
Patent Information
- Application Number
- CN202411303106.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-04-11
AI Technical Summary
The volume changes in the existing lithium battery negative electrode materials during charging and discharging lead to challenges in the electrode mechanical design, and the non-conductive characteristics of the prefabricated film increase the internal resistance of the electrode and reduce electrochemical performance.
A composite negative electrode material is used, in which a preformed film is coated on the surface of the negative electrode active material and conductive agent, and the conductive agent is dispersed in the preformed film, and the flexibility of the polymer material is used to buffer volume changes and reduce electron transport obstacles.
Effectively buffer the volume changes of the negative electrode material, extend the cell cycle life, while reducing the electrode internal resistance, and improving the electrochemical performance and cycle life of the battery.
Smart Images

Figure CN119812235A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and specifically to a composite negative electrode material, a negative electrode, a method for preparing a negative electrode, a battery and an electrical device. Background Art
[0002] Commonly used negative electrode materials in lithium battery production, such as natural / artificial graphite, silicon oxygen, silicon carbon, etc., will undergo a certain degree of volume change due to changes in their own lattice structure when undergoing intercalation / alloying reactions with lithium ions, which will cause changes in the thickness of the negative electrode and the battery cell on a macro scale, bringing challenges to the mechanical design of the battery cell and the package. In addition, when the battery cell is working, the repeated volume expansion / contraction of the negative electrode material will also cause the natural solid-electrolyte interface (SEI) film to break and regenerate, ultimately leading to failure due to loss of active lithium and impedance growth.
[0003] In order to buffer the volume change of the negative electrode material and maintain the stability of the SEI film on the surface of the negative electrode material, a solution of pre-coating a layer of prefabricated film on the surface of the negative electrode material has been proposed and applied. The prefabricated film is generally a polymer material with a certain elastic modulus, which can buffer the volume expansion / contraction of the negative electrode active material during the operation of the battery cell. However, the polymer material used in the existing prefabricated coating will increase the internal resistance of the electrode and reduce the electrochemical performance of the battery due to its non-conductive characteristics. Summary of the invention
[0004] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is to propose a composite negative electrode material, a negative electrode, a method for preparing a negative electrode, a battery and an electrical device. In the composite negative electrode material of the present application, the prefabricated film is simultaneously coated on the surface of the negative electrode active material and the conductive agent, which is beneficial to improve the electron transmission between the negative electrode active material and the conductive agent, reduce the electrode impedance, and improve the electrochemical performance of the battery.
[0005] The first aspect of the present application proposes a composite negative electrode material. According to an embodiment of the present application, the composite negative electrode material includes a negative electrode active material, a conductive agent and a prefabricated film; the prefabricated film is coated on the surface of the negative electrode active material particles, and the conductive agent is dispersed in the prefabricated film; the material of the prefabricated film includes a polymer material.
[0006] In the composite negative electrode material provided by the present application, the prefabricated film is coated on the particle surface of the negative electrode active material, and the conductive agent is dispersed in the prefabricated film, that is, the prefabricated film is coated with the active material and the conductive agent at the same time, which reduces the electron transmission barrier between the negative electrode active material and the conductive agent, helps to ensure the channel for electron transmission, thereby reducing resistance and improving the electrochemical performance of the battery. In addition, unlike the common carbon coating process, the prefabricated film is generally a tough polymer material, which can buffer the volume expansion / contraction of the negative electrode active material during the operation of the battery cell and extend the cycle life of the battery cell.
[0007] In a second aspect, the present application proposes a negative electrode, comprising a negative electrode current collector and a negative electrode active material layer; the negative electrode active material layer contains the above-mentioned composite negative electrode material.
[0008] The negative electrode provided in the present application comprises the above-mentioned composite negative electrode material, which can buffer the volume expansion / contraction of the negative electrode active material during the operation of the battery cell and extend the cycle life of the battery cell; at the same time, it is beneficial to reduce the electron transmission barrier between the negative electrode active material and the conductive agent, ensure the channel for electron transmission, thereby reducing resistance and improving the electrochemical performance of the battery.
[0009] The third aspect of the present application provides a method for preparing a negative electrode, comprising:
[0010] Mixing the negative electrode active material and the conductive agent to obtain a mixed material;
[0011] The mixed material is mixed with the monomer material to prepare a composite negative electrode material; the composite negative electrode material includes a negative electrode active material, a prefabricated film coated on the surface of the negative electrode active material particles, and a conductive agent dispersed in the prefabricated film, and the material of the prefabricated film is a polymer material formed by a polymerization reaction of the monomer material;
[0012] Mixing the composite negative electrode material with a binder to obtain a slurry;
[0013] The slurry is formed into a negative electrode active material layer on a negative electrode current collector to obtain a negative electrode.
[0014] The preparation method of the composite negative electrode material provided in the present application directly prepares the prefabricated film in the mixing process of electrode preparation without introducing new processes and equipment. In addition, the prefabricated film is directly coated on the surface of the composite negative electrode material and the conductive agent during the electrode preparation process, thereby reducing the electrode resistance and improving the battery cycle life. In addition, the prefabricated film is flexible and can buffer the volume expansion / contraction of the active material during the operation of the battery cell, thereby extending the cycle life of the battery cell.
[0015] In a fourth aspect, the present application proposes a battery, comprising the above-mentioned negative electrode, or the negative electrode prepared by the above-mentioned preparation method.
[0016] The battery provided in the present application, comprising the above-mentioned negative electrode, has low resistance and good cycle life.
[0017] The fifth aspect of the present application proposes an electrical device comprising the above-mentioned battery.
[0018] The electrical equipment provided in the present application comprises the above-mentioned battery, so that the electrical equipment has high safety and good service life.
[0019] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0021] Figure 1 Schematic diagram of the structure of the composite negative electrode material in the embodiment of the present application; wherein, Figure 1 The meanings of the reference numerals are: 1-prefabricated membrane, 2-negative electrode active material, 3-carbon black, 4-carbon nanotube.
[0022] Figure 2 It is a flow chart of a method for preparing a negative electrode in one embodiment of the present application.
[0023] Figure 3 It is a flow chart of a method for preparing a negative electrode in one embodiment of the present application.
[0024] Figure 4 It is a flow chart of a method for preparing a negative electrode in one embodiment of the present application.
[0025] Figure 5 It is a flow chart of a method for preparing a negative electrode in one embodiment of the present application. DETAILED DESCRIPTION
[0026] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.
[0027] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.
[0028] The endpoints and any values of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this application.
[0029] In the present application, the terms "comprise" or "include" are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0030] At present, in order to buffer the volume change of the negative electrode material and maintain the stability of the SEI film on the surface of the negative electrode material, a solution of coating the surface of the negative electrode material with a prefabricated film has been proposed and applied. The prefabricated film is generally a polymer material with a certain elastic modulus. However, most of the existing prefabricated films are applied at the material powder level. Coating the surface of the negative electrode material with a polymer with poor conductivity will hinder the electron transfer between the negative electrode material and the conductive agent, and increase the impedance of the electrode.
[0031] To this end, the first aspect of the embodiment of the present application proposes a composite negative electrode material. According to the embodiment of the present application, the composite negative electrode material includes a negative electrode active material, a conductive agent and a prefabricated film; the prefabricated film is coated on the surface of the negative electrode active material particles, and the conductive agent is dispersed in the prefabricated film; the material of the prefabricated film includes a polymer material.
[0032] In the embodiments of the present application, the "conductive agent is dispersed in the prefabricated film" is recorded. For any conductive agent particle, it can be completely located in the prefabricated film or partially located in the prefabricated film; preferably, most of the conductive agent particles or all of the conductive agent particles are located in the prefabricated film. Taking the conductive agent as a combination of carbon black and carbon nanotubes as an example, the structure of the composite negative electrode material is as follows Figure 1 shown.
[0033] In the composite negative electrode material provided in the embodiment of the present application, the prefabricated film is coated on the particle surface of the negative electrode active material, and the conductive agent is dispersed in the prefabricated film, that is, the prefabricated film simultaneously coats the active material and the conductive agent, reduces the electron transmission barrier between the negative electrode active material and the conductive agent, and is beneficial to ensure the channel for electron transmission, thereby reducing resistance and improving the electrochemical performance of the battery.
[0034] In addition, unlike the common carbon coating process, the prefabricated film is generally made of a tough polymer material, which can buffer the volume expansion / contraction of the negative electrode active material during the operation of the battery cell and extend the cycle life of the battery cell.
[0035] According to the embodiments of the present application, at least one of the following (1) to (3) is satisfied:
[0036] (1) The negative electrode active material includes at least one of graphite, soft carbon, hard carbon, silicon-based material and tin-based material;
[0037] (2) the conductive agent comprises at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers;
[0038] (3) The polymer material includes amine polymers.
[0039] In the present application, the negative electrode active material may be a negative electrode active material for a battery known in the art. As an example, the negative electrode active material in the embodiment of the present application may include at least one of graphite, soft carbon, hard carbon, silicon-based material and tin-based material.
[0040] Further, the silicon-based material may include at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys.
[0041] Further, the tin-based material may include at least one of elemental tin, tin oxide compounds, and tin alloys.
[0042] In the present application, the conductive agent may be a conductive agent for batteries known in the art. As an example, the conductive agent in the embodiment of the present application includes at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0043] In the embodiments of the present application, the polymer material includes an amine polymer. The amine radical of the amine polymer contains nitrogen and oxygen elements and has rich functional groups that can interact with the surface of the negative electrode active material, the binder, etc. to enhance the adhesion, thereby improving the structural stability. It can effectively buffer the volume expansion / contraction of the negative electrode active material during the operation of the battery cell and extend the cycle life of the battery cell.
[0044] According to the embodiments of the present application, at least one of the following (1) to (3) is satisfied:
[0045] (1) The negative electrode active material includes at least one of graphite and silicon-based materials;
[0046] (2) the conductive agent includes at least one of carbon black and carbon nanotubes;
[0047] (3) The polymer material includes at least one of polydopamine, polyaniline and polycaprolactam.
[0048] In the embodiment of the present application, the active material includes at least one of graphite and silicon-based materials. In practical applications, graphite and silicon-based materials exhibit good electrochemical properties and have good market application value; when the battery cell is working, the repeated volume expansion / contraction of these negative electrode active materials easily causes the natural solid-electrolyte interface (SEI) film to break, and the coating of the prefabricated film can provide good protection for such easily swellable materials. Further, the active material includes at least one of graphite, silicon oxide compounds and silicon-carbon composites.
[0049] In the embodiment of the present application, the conductive agent includes at least one of carbon black and carbon nanotubes. Further, the conductive agent includes a combination of carbon black and carbon nanotubes. By dispersing carbon black and carbon nanotubes in the prefabricated film, it is beneficial to increase the contact area between the conductive agent and the negative electrode active material, and build a good electron transmission path.
[0050] In the embodiment of the present application, the polymer material includes at least one of polydopamine, polyaniline and polycaprolactam. These polymers have abundant functional groups that can interact with the surface of the negative electrode active material, the binder, etc. to enhance the bonding property, which is beneficial to improve the structural stability; at the same time, it is easy to prepare and obtain a polymer with a certain elastic modulus.
[0051] According to the embodiments of the present application, the structural formula of the polymer material is shown in formula (I):
[0052]
[0053] The polymer polydopamine shown in formula (I) provided in the embodiment of the present application has abundant imino groups and hydroxyl groups, has high electronegativity, and can be adsorbed on the surface of the negative electrode active material through intermolecular forces, thereby improving the stability of the prefabricated film. When the composite negative electrode material is mixed with a binder to make a negative electrode, polydopamine can cross-link with the binder to form a network structure, thereby improving the structural stability of the negative electrode.
[0054] In the present application, the particle size of the negative electrode active material can be the particle size known in the art for use in batteries. The particle size of the conductive agent can be the particle size known in the art for use in batteries. Generally, the particle size of the conductive agent is smaller than the particle size of the negative electrode active material.
[0055] According to an embodiment of the present application, the particle size of the conductive agent is smaller than the particle size of the negative electrode active material, and the conductive agent may be dispersed in the prefabricated film.
[0056] According to the embodiments of the present application, at least one of the following (1) to (3) is satisfied:
[0057] (1) The average particle size of the negative electrode active material is 1 μm to 20 μm;
[0058] (2) The average particle size of the conductive agent is 30 nm to 100 nm;
[0059] (3) The thickness of the prefabricated film is 10nm to 200nm.
[0060] In the embodiment of the present application, the average particle size of the negative electrode active material is 1 μm to 20 μm. In a specific example, the average particle size of the negative electrode active material is 1 μm, 3 μm, 5 μm, 7 μm, 9 μm, 11 μm, 13 μm, 15 μm, 17 μm, 19 μm or 20 μm, etc. The average particle size of the negative electrode active material meets the above conditions, which is conducive to promoting the battery to obtain good charge and discharge performance and cycle stability, and is also conducive to uniform coating of the prefabricated film.
[0061] In the embodiment of the present application, the average particle size of the conductive agent is 30nm to 100nm. In the specific example, the average particle size of the conductive agent is 30nm, 31nm, 32nm, 33nm, 34nm, 35nm, 36nm, 37nm, 38nm, 39nm, 40nm, 41nm, 42nm, 43nm, 44nm, 45nm, 46nm, 47nm, 48nm, 49nm, 50nm, 51nm, 52nm, 53nm, 54nm, 55nm, 56nm, 57nm, 58nm, 59nm, 60nm, 61nm, 62nm, 63nm, 64nm, 65nm, 66nm, 67nm, 68nm, 69nm, 70nm, 71nm, 72nm, 73nm, 74nm, 75nm, 76nm, 77nm, 78nm, 79nm, 80nm, 81nm 1nm, 62nm, 63nm, 64nm, 65nm, 66nm, 67nm, 68nm, 69nm, 70nm, 71nm, 72nm, 73nm, 74nm, 75nm, 76nm, 77nm, 78nm, 79nm, 80nm, 81nm, 82nm, 83nm, 84nm, 85nm, 86nm, 87nm, 88nm, 89nm, 90nm, 91nm, 92nm, 93nm, 94nm, 95nm, 96nm, 97nm, 98nm, 99nm, 100nm. The average particle size of the conductive agent meets the above conditions. In practical applications, based on the average particle size of the negative electrode active material, a particle size smaller than the negative electrode active material is selected to ensure that the conductive agent can be evenly dispersed in the prefabricated film, which is beneficial to reducing the internal resistance of the electrode.
[0062] In the embodiment of the present application, the thickness of the prefabricated film is 10nm to 200nm. In the specific example, the thickness of the prefabricated film is 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 90nm, 100nm, 150nm, 200nm, etc. Since the conductivity of the polymer material itself is poor, the conductivity of the electrode will be affected after the prefabricated film layer. In the embodiment of the application, the thickness of the prefabricated film meets the above conditions. On the one hand, a stable structure is obtained to buffer the volume change of the negative electrode material without being destroyed; on the other hand, it is conducive to obtaining a lower electrode internal resistance and improving the long cycle life of the battery.
[0063] In the embodiment of the present application, the average particle size of the negative electrode active material is 1 μm to 20 μm, the average particle size of the conductive agent is 30 nm to 100 nm, and the thickness of the prefabricated film is 10 nm to 200 nm.
[0064] The three work together to form a uniform and stable pre-film coating layer on the surface of the negative electrode active material particles. The conductive agent is evenly dispersed in the pre-film, which is beneficial to reduce the electron transmission barrier, reduce the internal resistance of the electrode, and increase the cycle life of the battery.
[0065] According to the embodiments of the present application, the composite negative electrode material includes, by weight: 80 to 96 parts of negative electrode active material; 0.001 to 2.0 parts of conductive agent; and 0.5 to 3 parts of prefabricated film.
[0066] In the embodiment of the present application, the amount of each component in the composite negative electrode material meets the above conditions, which is conducive to obtaining a stable composite negative electrode material, while also helping to reduce the electrode resistance and increase the cycle life of the battery. Among them. The content of the prefabricated film meets the above conditions, while ensuring that it provides a good buffering effect for the negative electrode active material, it is conducive to maintaining a low electrode internal resistance.
[0067] Furthermore, the prefabricated film is 1 to 2.5 parts, such as 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2.0 parts, 2.2 parts, 2.4 parts and 2.5 parts.
[0068] In the embodiments of the present application, the prefabricated film meets the above conditions, achieves an effective buffering effect on the negative electrode active material, and at the same time, effectively coats the negative electrode active material and the conductive agent to reduce the internal resistance of the electrode.
[0069] A second aspect of an embodiment of the present application provides a negative electrode, comprising a negative electrode current collector and a negative electrode active material layer; the negative electrode active material layer contains the above-mentioned composite negative electrode material.
[0070] The negative electrode provided in the embodiment of the present application comprises the above-mentioned composite negative electrode material, which can buffer the volume expansion / contraction of the negative electrode active material during the operation of the battery cell and extend the cycle life of the battery cell; at the same time, it is beneficial to reduce the electron transmission barrier between the negative electrode active material and the conductive agent, ensure the channel for electron transmission, thereby reducing resistance and improving the electrochemical performance of the battery.
[0071] According to the embodiment of the present application, the negative electrode active material layer includes the following components in terms of mass percentage: negative electrode active material, 93% to 96%; prefabricated film, 0.5% to 3%; conductive agent, 0.001% to 2.0%; binder, 0.5% to 2.5%. In a specific example, each component can arbitrarily select its content value within its respective percentage range, as long as the sum of the contents of all components is 100%. The mass percentage of the prefabricated film can be 0.5%, 1%, 0.5%, 1.5%, 2%, 2.5% or 3%, etc.
[0072] In the embodiments of the present application, the mass percentage of each component meets the above conditions, and the components work together to obtain a stable electrode and exhibit good electrochemical performance. The prefabricated film is coated on the surface of the negative electrode active material particles, and the conductive agent is dispersed in the prefabricated film. On the one hand, it provides an effective buffering effect on the negative electrode active material, and on the other hand, it is conducive to ensuring the electron transmission channel and reducing the internal resistance of the electrode. At the same time, the prefabricated film forms a stable cross-linked network structure through the polar groups it carries and the binder adsorbed, further improving the stability and electrochemical performance of the negative electrode.
[0073] According to an embodiment of the present application, the negative electrode active material layer includes the following components, calculated by mass percentage: negative electrode active material, 93% to 96%; polydopamine, 1% to 2.5%; conductive agent, 0.001% to 2.0%; and binder, 0.5% to 2.5%.
[0074] In the examples of the present application, the mass percentage of each component meets the above conditions, and the components work together to obtain a stable electrode and exhibit good electrochemical performance.
[0075] According to an embodiment of the present application, the negative electrode active material layer includes the following components, calculated by mass percentage: graphite, 88% to 96%; silicon oxide / silicon carbon composite, 0% to 10%; polydopamine, 1% to 2.5%; conductive agent, 0.001% to 2.0%; and binder, 0.5% to 2.5%.
[0076] In the embodiments of the present application, the mass percentage of each component meets the above conditions, and the components work together to further obtain a stable electrode and exhibit good electrochemical performance.
[0077] According to an embodiment of the present application, the negative electrode current collector may adopt a current collector conventionally used for batteries in the art. In a specific example, the negative electrode current collector includes a metal foil or a composite current collector. For example, copper foil can be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).
[0078] The third aspect of the embodiment of the present application provides a method for preparing a negative electrode, comprising:
[0079] Mixing the negative electrode active material and the conductive agent to obtain a mixed material;
[0080] The mixed material is mixed with the monomer material to prepare a composite negative electrode material; the composite negative electrode material includes a negative electrode active material, a prefabricated film coated on the surface of the negative electrode active material particles, and a conductive agent dispersed in the prefabricated film, and the material of the prefabricated film is a polymer material formed by a polymerization reaction of the monomer material;
[0081] Mixing the composite negative electrode material with a binder to obtain a slurry;
[0082] The slurry is formed into a negative electrode active material layer on a negative electrode current collector to obtain a negative electrode.
[0083] In this application, the "monomer material" recorded refers to the monomer used to form the polymer material through polymerization reaction. In order to realize or promote the effective progress of the polymerization reaction, auxiliary reagents such as initiators and catalysts may be added.
[0084] In the prior art, the preparation methods of artificial prefabricated membranes are all applied to the negative electrode material powder level. It is necessary to first coat the artificial prefabricated membrane on the negative electrode active material powder level and then prepare the electrode, which is not compatible with the current mass production process of battery cells and increases the process steps and costs. The preparation method of the composite negative electrode material provided in the embodiment of the present application directly prepares the artificial prefabricated membrane in the mixing process of electrode preparation without introducing new processes and equipment. And the artificial prefabricated membrane is directly coated on the surface of the composite negative electrode material and the conductive agent at the same time during the electrode preparation process, thereby reducing the electrode resistance and improving the battery's long cycle life. In addition, the artificial prefabricated membrane has flexibility, which can buffer the volume expansion / contraction of the active material during the operation of the battery cell and extend the cycle life of the battery cell.
[0085] In a specific example, the preparation method of the negative electrode is as follows: Figure 2 As shown, the steps include:
[0086] S1000: mixing the negative electrode active material and the conductive agent to obtain a mixed material;
[0087] S2000: mixing the mixed material with the monomer material to prepare a composite negative electrode material;
[0088] S3000: mixing the composite negative electrode material with a binder to obtain a slurry;
[0089] S4000: The slurry is applied to the negative electrode current collector to form a negative electrode active material layer to obtain a negative electrode. After the slurry is applied to the negative electrode current collector, the negative electrode can be further obtained by drying, compacting, and cutting.
[0090] According to the embodiments of the present application, at least one of the following (1) to (3) is satisfied:
[0091] (1) The negative electrode active material includes at least one of graphite, soft carbon, hard carbon, silicon-based material and tin-based material;
[0092] (2) the conductive agent comprises at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers;
[0093] (3) The polymer material includes amine polymers.
[0094] In the present application, the negative electrode active material may be a negative electrode active material for a battery known in the art. As an example, the negative electrode active material in the embodiment of the present application may include at least one of graphite, soft carbon, hard carbon, silicon-based material and tin-based material.
[0095] Further, the silicon-based material may include at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys.
[0096] Further, the tin-based material may include at least one of elemental tin, tin oxide compounds, and tin alloys.
[0097] In the present application, the conductive agent may be a conductive agent for batteries known in the art. As an example, the conductive agent in the embodiment of the present application includes at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0098] In the embodiments of the present application, the polymer material includes an amine polymer. The amine radical of the amine polymer contains nitrogen and oxygen elements and has rich functional groups that can interact with the surface of the negative electrode active material, the binder, etc. to enhance the adhesion, thereby improving the structural stability. It can effectively buffer the volume expansion / contraction of the negative electrode active material during the operation of the battery cell and extend the cycle life of the battery cell.
[0099] According to the embodiments of the present application, at least one of the following (1) to (3) is satisfied:
[0100] (1) The negative electrode active material includes at least one of graphite and silicon-based materials;
[0101] (2) the conductive agent includes at least one of carbon black and carbon nanotubes;
[0102] (3) The polymer material includes at least one of polydopamine, polyaniline and polycaprolactam.
[0103] In the embodiment of the present application, the active material includes at least one of graphite and silicon-based materials. In practical applications, graphite and silicon-based materials show good electrochemical properties and have good market application value. Further, the active material includes at least one of graphite, silicon-oxygen compounds and silicon-carbon composites.
[0104] In the embodiment of the present application, the conductive agent includes at least one of carbon black and carbon nanotubes. Further, the conductive agent includes a combination of carbon black and carbon nanotubes. By dispersing carbon black and carbon nanotubes in the prefabricated film, it is beneficial to increase the contact area between the conductive agent and the negative electrode active material, and build a good electron transmission path.
[0105] In the embodiment of the present application, the polymer material includes at least one of polydopamine, polyaniline and polycaprolactam. These polymers have abundant functional groups that can interact with the surface of the negative electrode active material, the binder, etc. to enhance the bonding property, which is beneficial to improve the structural stability; at the same time, it is easy to prepare and obtain a polymer with a certain elastic modulus.
[0106] According to the embodiments of the present application, the structural formula of the polymer material is shown in formula (I):
[0107]
[0108] The polymer polydopamine shown in formula (I) provided in the embodiment of the present application has abundant imino groups and hydroxyl groups, has high electronegativity, and can be adsorbed on the surface of the negative electrode active material through intermolecular forces, thereby improving the stability of the prefabricated film. When the composite negative electrode material is mixed with a binder to make a negative electrode, polydopamine can cross-link with the binder to form a network structure, thereby improving the structural stability of the negative electrode.
[0109] In the present application, the particle size of the negative electrode active material can be the particle size known in the art for use in batteries. The particle size of the conductive agent can be the particle size known in the art for use in batteries. Generally, the particle size of the conductive agent is smaller than the particle size of the negative electrode active material.
[0110] According to an embodiment of the present application, the particle size of the conductive agent is smaller than the particle size of the negative electrode active material, and the conductive agent may be dispersed in the prefabricated film.
[0111] According to the embodiments of the present application, the raw materials used in the preparation method include the following components, calculated by mass percentage: negative electrode active material, 93% to 96%; monomer material, 1.0% to 2.5%; conductive agent, 0.001% to 2.0%; binder, 0.5% to 2.5%. In a specific example, each component can arbitrarily select its content value within its respective percentage range, as long as the sum of the contents of all components is 100%. The mass percentage of the prefabricated membrane can be 0.5%, 1%, 0.5%, 1.5%, 2%, 2.5% or 3%, etc.
[0112] In the embodiments of the present application, the mass percentage of each component meets the above conditions, and the components work together to obtain a stable electrode and exhibit good electrochemical performance. The prefabricated film is coated on the surface of the negative electrode active material particles, and the conductive agent is dispersed in the prefabricated film. On the one hand, it provides an effective buffering effect on the negative electrode active material, and on the other hand, it is conducive to ensuring the electron transmission channel and reducing the internal resistance of the electrode. At the same time, the prefabricated film forms a stable cross-linked network structure through the polar groups it carries and the binder adsorbed, further improving the stability and electrochemical performance of the negative electrode.
[0113] According to an embodiment of the present application, the monomer material includes a water-soluble monomer material; preferably, the water-soluble monomer material includes at least one of aniline and dopamine hydrochloride.
[0114] In the embodiment of the present application, the monomer material is a water-soluble monomer material, which can be polymerized in an aqueous solvent environment to generate a polymer material for a prefabricated membrane.
[0115] Different from some monomer materials of artificial prefabricated membranes that are not water-soluble, the embodiments of the present application use water-soluble monomer materials, which match the current negative electrode mixing process and can directly prepare artificial prefabricated membranes in the mixing process of electrode preparation without introducing new processes, materials and equipment. In addition, water-soluble monomer materials are used as raw materials for prefabricated membranes, and organic solvents are not introduced, so there is no risk of toxic solvent volatilization and solvent recovery requirements.
[0116] Furthermore, in the embodiment of the present application, the water-soluble monomer material includes at least one of aniline and dopamine hydrochloride. The water-soluble dopamine monomer is used as the artificial SEI material, and no organic solvent is introduced, and there is no risk of toxic solvent volatilization and solvent recovery requirements, which can be well matched with the existing negative electrode mixing process.
[0117] According to an embodiment of the present application, a method for preparing a composite negative electrode material comprises the steps of:
[0118] Mixing the negative electrode active material and the conductive agent to obtain a mixed material;
[0119] The mixed material is mixed with an aqueous solution of dopamine hydrochloride to prepare a composite negative electrode material; the composite negative electrode material comprises a negative electrode active material, a prefabricated film coated on the surface of the negative electrode active material particles and a conductive agent dispersed in the prefabricated film, and the material of the prefabricated film is polydopamine formed by polymerization reaction of dopamine hydrochloride;
[0120] Mixing the composite negative electrode material with a binder to obtain a slurry;
[0121] The slurry is formed into a negative electrode active material layer on a negative electrode current collector to obtain a negative electrode.
[0122] In the embodiment of the present application, in the step of preparing the composite negative electrode material, dopamine hydrochloride is used as the monomer material. Dopamine hydrochloride is a water-soluble monomer. The dopamine hydrochloride aqueous solution can be directly added into the mixing process. Correspondingly, in the process of mixing the composite negative electrode material and the binder, it can be completed in an aqueous solvent environment, which matches the existing negative electrode mixing process. Compared with the non-aqueous solvent environment, it is beneficial to save costs and simplify the preparation process.
[0123] In a specific example, a method for preparing a composite negative electrode material is as follows: Figure 3 As shown, the steps include:
[0124] S1000: mixing the negative electrode active material and the conductive agent to obtain a mixed material;
[0125] S2000: mixing the mixed material with an aqueous solution of dopamine hydrochloride to prepare a composite negative electrode material;
[0126] S3000: mixing the composite negative electrode material with an aqueous solution of a binder to obtain a slurry;
[0127] S4000: coating the slurry on the negative electrode current collector to form a negative electrode active material layer to obtain a negative electrode.
[0128] 18. According to an embodiment of the present application, in the step of mixing the mixed material with an aqueous solution of dopamine hydrochloride to prepare a composite negative electrode material: a Tris buffer solution is also added to adjust the pH of the mixed material and the aqueous solution of dopamine hydrochloride.
[0129] In this application, the "Tris buffer solution" described is a buffer solution prepared from trisaminomethane, salt and distilled water.
[0130] In the embodiment of the present application, in the step of preparing the composite negative electrode material, a Tris buffer solution is added to adjust the pH value of the reaction environment to promote the effective polymer reaction.
[0131] In a specific example, a method for preparing a composite negative electrode material is as follows: Figure 4 As shown, the steps include:
[0132] S1000: mixing the negative electrode active material and the conductive agent to obtain a mixed material;
[0133] S2000: mixing the mixed material with an aqueous solution of dopamine hydrochloride, and then adding a Tris buffer solution to adjust the pH value to prepare a composite negative electrode material;
[0134] S3000: mixing the composite negative electrode material with an aqueous solution of a binder to obtain a slurry;
[0135] S4000: coating the slurry on the negative electrode current collector to form a negative electrode active material layer to obtain a negative electrode.
[0136] In a specific example, a method for preparing a composite negative electrode material is as follows: Figure 5 As shown, the steps include:
[0137] S1000: Mix the negative electrode active material and the conductive agent to obtain a mixed material. In order to improve the mixing uniformity, mechanical stirring and mixing can be used. Further, the stirring parameters are controlled to include: the revolution speed is 10rpm to 50rpm, the rotation speed is 400rpm to 700rpm, and the stirring time is 5min to 20min.
[0138] S2000: Mix the mixed material with an aqueous solution of dopamine hydrochloride, and then add a Tris buffer solution to adjust the pH value to prepare a composite negative electrode material. In order to promote the polymerization reaction, it can be carried out under stirring conditions. Further, the stirring parameters are controlled to include: the revolution speed is 30rpm to 80rpm, the rotation speed is 500rpm to 800rpm, and the stirring time is 0.5h to 2h.
[0139] S3000: Mix the composite negative electrode material with the aqueous solution of sodium carboxymethyl cellulose to obtain a first slurry. In order to improve the mixing uniformity, mechanical stirring and mixing can be used. Further, the stirring parameters are controlled to include: the revolution speed is 30 rpm to 100 rpm, the rotation speed is 800 rpm to 2500 rpm, and the stirring time is 0.5 h to 2 h.
[0140] S4000: Add styrene-butadiene rubber (SBR) or polyacrylic acid (PAA) and mix to obtain a second slurry. In order to improve the mixing uniformity, mechanical stirring and mixing can be used. Further, the stirring parameters include: the revolution speed is 10 rpm to 50 rpm, the rotation speed is 200 rpm to 800 rpm, and the stirring time is 0.5 h to 1 h.
[0141] S5000: coating the second slurry on the negative electrode current collector to obtain a negative electrode.
[0142] Furthermore, after step S4000, the second slurry can be taken to test its solid content and viscosity, and the solid content range is controlled to be 40% to 65%, and the viscosity range is 800cp to 2500cp.
[0143] According to an embodiment of the present application, in the step of mixing the mixed material with an aqueous solution of dopamine hydrochloride to prepare a composite negative electrode material, the control parameters include at least one of the following (1) to (3):
[0144] (1) The mass concentration of dopamine hydrochloride is 3% to 8%;
[0145] (2) The concentration of Tris buffer solution is 0.05M to 0.15M;
[0146] (3) The pH of the mixture of the mixture and the aqueous solution of dopamine hydrochloride is adjusted to 7.5-9 by using a Tris buffer solution.
[0147] In the embodiment of the present application, in the step of mixing the mixed material with the aqueous solution of dopamine hydrochloride to prepare the composite negative electrode material, the mass concentration of dopamine hydrochloride is controlled to be 3% to 8%, and specific examples are 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5% or 8%, etc. In the embodiment of the present application, the mass concentration of dopamine hydrochloride meets the above conditions, which is conducive to promoting the formation of the prefabricated film, forming a polydopamine polymer, and uniformly coating the negative electrode active material and the conductive agent.
[0148] Furthermore, the mass concentration of dopamine hydrochloride is controlled to be 4% to 7%, with specific examples being 4%, 4.2%, 4.4%, 4.6%, 4.8%, 5%, 5.2%, 5.4%, 5.6%, 5.8%, 6%, 6.2%, 6.4%, 6.6%, 6.8% or 7%, etc.
[0149] In the embodiment of the present application, the concentration of the Tris buffer solution is 0.05M to 0.15M, and specific examples are 0.05M, 0.07M, 0.09M, 0.1M, 0.11M, 0.13M or 0.15M, etc. In the embodiment of the present application, the Tris buffer solution is used to adjust the pH value of the polymerization reaction and acts as an initiator. The concentration of the Tris buffer solution meets the above conditions and can effectively promote the polymerization reaction to generate the target polydopamine product.
[0150] Furthermore, the concentration of the Tris buffer solution is 0.1M.
[0151] In the embodiment of the present application, the pH of the mixture of the mixture and the aqueous solution of dopamine hydrochloride is adjusted by the Tris buffer solution to 7.5 to 9. In a specific example, the pH is 7.5, 7.7, 7.9, 8.1, 8.3, 8.5, 8.7, 8.9 or 9. In the embodiment of the present application, the polymerization reaction is carried out in a weakly alkaline environment, the polymerization efficiency is better, and the target polydopamine prefilm is formed, which can be evenly coated on the surface of the negative electrode active material and the conductive agent.
[0152] Furthermore, the pH of the mixture of the mixture and the aqueous solution of dopamine hydrochloride is adjusted by the Tris buffer solution to 8 to 8.5, and specific examples thereof are 8.1, 8.2, 8.3, 8.4 or 8.5.
[0153] A fourth aspect of the embodiments of the present application provides a battery, comprising the above-mentioned negative electrode, or the negative electrode prepared by the above-mentioned preparation method.
[0154] The battery provided in the embodiment of the present application, comprising the above-mentioned negative electrode, has lower resistance and good cycle life.
[0155] According to an embodiment of the present application, the battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays a role in conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0156] According to an embodiment of the present application, the battery includes a lithium ion battery or a sodium ion battery.
[0157] A fifth aspect of the embodiments of the present application provides an electrical device comprising the above-mentioned battery.
[0158] The electric device provided in the embodiment of the present application comprises the above-mentioned battery, so that the electric device has high safety and good service life.
[0159] Battery cells, battery modules, and battery packs can be used as power sources for electrical devices or as energy storage units for electrical devices. Electrical devices may include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc.
[0160] As an electrical device, a battery cell, battery module or battery pack can be selected according to its usage requirements.
[0161] As an embodiment, the electric device may be a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, etc.
[0162] As another embodiment, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.
[0163] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.
[0164] Example 1
[0165] This embodiment provides a negative electrode sheet, including a negative electrode current collector and a negative electrode active material layer, the components of the negative electrode active material layer are graphite, silicon oxide, carbon black, polydopamine, sodium carboxymethyl cellulose (CMC-Na) and styrene-butadiene rubber (SBR), and the corresponding weight percentages of each component are 91%, 5.0%, 0.8%, 2.0%, 0.6%, and 0.6, respectively. Prepared by the following method:
[0166] Step 1: Add the negative electrode active material (graphite and silicon oxide) and the conductive agent (carbon black) into the stirring tank and stir at an orbital speed of 25 rpm and an autorotational speed of 550 rpm for 15 minutes. During this period, scrape off the material powder attached to the wall of the stirring tank and stir evenly.
[0167] Step 2: Add 6% dopamine hydrochloride (molecular formula: C 8 H 12 ClNO 2) aqueous solution, after mixing evenly, add 0.1M Tris buffer solution, adjust the slurry pH value to 8, continue stirring to allow dopamine to polymerize, the revolution speed is 50 rpm, the rotation speed is 600 rpm, and the stirring time is 1 hour.
[0168] Step 3: Add the aqueous solution of sodium carboxymethyl cellulose to the stirring tank and continue stirring at an orbital speed of 60 rpm, an autorotational speed of 1500 rpm, and a stirring time of 1.5 h.
[0169] Step 4: Add styrene-butadiene rubber (SBR) into the stirring tank and continue stirring at an orbital speed of 30 rpm, an autorotational speed of 500 rpm, and a stirring time of 1 hour.
[0170] Step 5: Slurry sampling and testing, the solid content is within the range of 40% to 65%, and the viscosity is within the range of 800cp to 2500cp.
[0171] Step 6: After the slurry is formed, it is transferred to a buffer tank, sieved, and evenly coated on a smooth copper foil by a coating machine, and dried in an oven to obtain a negative electrode sheet.
[0172] Preparation of lithium-ion batteries:
[0173] (1) Negative electrode sheet: The negative electrode sheet prepared in this embodiment is used.
[0174] (2) Positive electrode sheet: The positive electrode active material LFP (lithium iron phosphate, Lithium Iron Phosphate, chemical formula LiFePO 4 ), carbon nanotubes, and binder PVDF (polyvinylidene fluoride) are mixed in a mass ratio of 96%, 1.8%, and 2.2%, and a solvent NMP (N-methyl-2-pyrrolidone) is added and stirred evenly in a stirring tank. The positive electrode slurry is then coated on a smooth aluminum foil and dried in an oven to obtain a positive electrode sheet.
[0175] (3) Preparation of lithium-ion batteries: The positive and negative electrode sheets are subjected to standard process flow such as rolling, die-cutting, winding, assembly, liquid injection, formation, and aging to obtain lithium-ion batteries.
[0176] Example 2-Example 4
[0177] Examples 2 to 4 respectively provide a negative electrode sheet, including a negative electrode current collector and a negative electrode active material layer, and the composition of the negative electrode active material layer is shown in Table 1. The unit of the amount of each component is mass percentage; the binder is a combination of CMC-Na and SBR, and the mass ratio of the two is 1:1.
[0178] The specific preparation method of the negative electrode plate is as shown in Example 1, except that the monomer material is replaced by aniline.
[0179] Preparation of lithium-ion battery: The method is as shown in Example 1.
[0180] Table 1 Composition of the active material layer of Example 2-Example 4
[0181]
[0182] Example 5-Example 9
[0183] Examples 5 to 9 respectively provide a negative electrode sheet, including a negative electrode current collector and a negative electrode active material layer. The composition of the negative electrode active material layer is as shown in Example 1.
[0184] The specific preparation method of the negative electrode plate is as shown in Example 1, except that: the control parameter values in step 2 are different, as shown in Table 2.
[0185] Preparation of lithium-ion battery: The method is as shown in Example 1.
[0186] Table 2 Process parameters of the negative electrode preparation method provided by Examples 5 to 9
[0187] sample Mass fraction of dopamine hydrochloride pH Example 5 3% 8 Example 6 8% 8 Example 7 6% 7.5 Example 8 6% 8.5 Example 9 6% 9
[0188] Comparative Example 1
[0189] This comparative example provides a negative electrode plate, including a negative electrode current collector and a negative electrode active material layer. The components of the negative electrode active material layer are graphite, silicon oxide, carbon black, CMC-Na and SBR, and the corresponding weight percentages of each component are 91%, 5.0%, 1.8%, 1.1% and 1.1% respectively.
[0190] The specific preparation method of the negative electrode plate is as shown in Example 1, except that step 2 is not performed, and the remaining steps are the same.
[0191] The method for preparing a lithium ion battery is shown in Example 1.
[0192] Comparative Example 2
[0193] This comparative example provides a negative electrode plate, including a negative electrode current collector and a negative electrode active material layer, the components of the negative electrode active material layer are artificial SEI-coated graphite / silicon oxide, carbon black, CMC-Na and SBR, and the corresponding weight percentages of each component are 98%, 0.8%, 0.6% and 0.6%, respectively.
[0194] The specific preparation method of the negative electrode sheet is as shown in Example 1, except that:
[0195] Step 1: Disperse graphite powder, silicon oxide and dopamine hydrochloride in deionized water at a mass ratio of 91:5:2.0, add 0.1M Tris buffer solution, adjust the slurry pH value range to 8, and continue stirring for 1.5 hours to polymerize dopamine on the surface of graphite powder. Sieve and dry the slurry to obtain a prefabricated membrane-coated graphite / silicon oxide material.
[0196] Step 2: Add the prefabricated membrane-coated graphite / silicon oxide material and the conductive agent (carbon black) into the stirring tank and stir at an orbital speed of 25 rpm and an autorotational speed of 550 rpm for 15 minutes. During this period, the material powder attached to the wall of the stirring tank is scraped off and stirred evenly.
[0197] Step 3: Add the aqueous solution of CMC-Na into the stirring tank and continue stirring at an orbital speed of 60 rpm, an autorotational speed of 1500 rpm, and a stirring time of 1.5 h.
[0198] Step 4: Add SBR into the stirring tank and continue stirring at an orbital speed of 30 rpm, an autorotational speed of 500 rpm, and a stirring time of 1 hour.
[0199] Step 5: Slurry sampling and testing, the solid content is within the range of 40% to 65%, and the viscosity is within the range of 800cp to 2500cp.
[0200] Step 6: After the slurry is formed, it is transferred to a buffer tank, sieved, and evenly coated on a smooth copper foil by a coating machine, and dried in an oven to obtain a negative electrode sheet.
[0201] The method for preparing a lithium ion battery is shown in Example 1.
[0202] Performance Testing
[0203] 1. Test method:
[0204] 1. Diaphragm resistance test: Cut the negative electrode sheet into 30mm×50mm sheets, peel the active material layer from the copper foil with tape, and test the diaphragm resistance with a diaphragm resistance tester.
[0205] 2. Post-cycle electrode thickness test: 25°C, 2.2V~3.65V, 0.33C. After 200 cycles, take out the negative electrode and measure the thickness of the negative electrode with a micrometer.
[0206] 3: DCIR test: At 25℃, adjust the battery to 50% SOC, discharge at 3C for 10s, and calculate the DCIR.
[0207] 4. 25℃ cycle test: 25℃, 2.2V~3.65V, 1C / 1C cycle for 1000 times, calculate the capacity retention rate.
[0208] 2. Test results:
[0209] Table 3 Performance test results of samples provided in various embodiments and comparative examples
[0210]
[0211] The performance test results are shown in Table 3.
[0212] Polydopamine is coated on the graphite / silicon oxide surface as a prefabricated film. Due to its non-conductive property, the resistance of the electrode after coating increases compared with the uncoated group (Comparative Example 1); but compared with the coating at the material particle level (Comparative Example 2), the conductive carbon black is coated on the surface of the negative electrode active material at the electrode level (Example 1-Example 9), which can ensure the electron transmission path. Therefore, the membrane resistance and DC impedance are only slightly increased compared with the uncoated group.
[0213] Since polydopamine can effectively buffer the breathing expansion of graphite / silicon oxide during the cycle, the thickness increase of the coated pole piece after 1000 cycles is reduced compared to the uncoated group; and because dopamine can cross-link with the binder during the polymerization process during the preparation of the pole piece level, further limiting the volume expansion after the cycle, so a similar inhibitory expansion effect can be achieved when the amount of polydopamine added is small (Example 3 and Comparative Example 2). Finally, since the breathing expansion of graphite / silicon oxide during the cycle is effectively suppressed by the artificial SEI of polydopamine, the breakage and regeneration of the native prefabricated film are reduced, thereby reducing the loss of active lithium. Therefore, compared with Comparative Example 1, the capacity retention rate of the remaining groups after 1000 cycles is improved, and the capacity retention rate of the pole piece level coating (Examples 1-9) is better than that of the material level coating (Comparative Example 2). In summary, the negative electrode provided herein with a polydopamine prefabricated film coated at the pole piece level has good comprehensive chemical performance.
[0214] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A composite negative electrode material, characterized in that: It includes negative electrode active material, conductive agent and prefabricated film; The prefabricated film is coated on the surface of the negative electrode active material particles, and the conductive agent is dispersed in the prefabricated film; The material of the prefabricated membrane includes a polymer material.
2. The composite negative electrode material according to claim 1, characterized in that: Satisfy at least one of the following (1) to (3): (1) The negative electrode active material includes at least one of graphite, soft carbon, hard carbon, silicon-based material and tin-based material; (2) The conductive agent includes at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers; (3) The polymer material includes an amine polymer.
3. The composite negative electrode material according to claim 1 or 2, characterized in that: Satisfy at least one of the following (1) to (3): (1) The negative electrode active material includes at least one of graphite and silicon-based materials; (2) The conductive agent includes at least one of carbon black and carbon nanotubes; (3) The polymer material includes at least one of polydopamine, polyaniline and polycaprolactam.
4. The composite negative electrode material according to any one of claims 1 to 3, characterized in that: The structural formula of the polymer material is shown in formula (I):
5. The composite negative electrode material according to any one of claims 1 to 4, characterized in that: Satisfy at least one of the following (1) to (3): (1) The average particle size of the negative electrode active material is 1 μm to 20 μm; (2) The average particle size of the conductive agent is 30 nm to 100 nm; (3) The thickness of the prefabricated film is 10 nm to 900 nm.
6. The composite negative electrode material according to any one of claims 1 to 5, characterized in that: In parts by weight, the composite negative electrode material comprises: Negative electrode active material, 80 to 96 parts; Conductive agent, 0.001 to 2.0 parts; Prefabricated film, 0.5 to 3 parts.
7. A negative electrode, characterized in that It comprises a negative electrode current collector and a negative electrode active material layer; the negative electrode active material layer comprises the composite negative electrode material according to any one of claims 1 to 6.
8. The negative electrode according to claim 7, characterized in that The negative electrode active material layer comprises the following components in terms of mass percentage: Negative electrode active material, 93% to 96%; Prefabricated membrane, 0.5% to 3%; Conductive agent, 0.001% to 2.0%; Binder: 0.5%~2.5%.
9. The negative electrode according to claim 7 or 8, characterized in that The negative electrode active material layer comprises the following components in terms of mass percentage: Negative electrode active material, 93% to 96%; Polydopamine, 1% to 2.5%; Conductive agent, 0.001% to 2.0%; Binder, 0.5%~2.5%.
10. A method for preparing a negative electrode, characterized in that: include: Mixing the negative electrode active material and the conductive agent to obtain a mixed material; The mixed material is mixed with a monomer material to prepare a composite negative electrode material; the composite negative electrode material comprises the negative electrode active material, a prefabricated film coated on the surface of the negative electrode active material particles and the conductive agent dispersed in the prefabricated film, and the material of the prefabricated film is a polymer material formed by a polymerization reaction of the monomer material; Mixing the composite negative electrode material with a binder to obtain a slurry; The slurry is used to form a negative electrode active material layer on a negative electrode current collector to obtain a negative electrode.
11. The preparation method according to claim 10, characterized in that: Satisfy at least one of the following (1) to (3): (1) The negative electrode active material includes at least one of graphite, soft carbon, hard carbon, silicon-based material and tin-based material; (2) The conductive agent includes at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers; (3) The polymer material includes an amine polymer.
12. The preparation method according to claim 10 or 11, characterized in that: Satisfy at least one of the following (1) to (3): (1) The negative electrode active material includes at least one of graphite and silicon-based materials; (2) The conductive agent includes at least one of carbon black and carbon nanotubes; (3) The polymer material includes at least one of polydopamine, polyaniline and polycaprolactam.
13. The preparation method according to any one of claims 10 to 12, characterized in that: Calculated by percentage, the raw materials used in the preparation method include the following components: Negative electrode active material, 96% to 96%; Monomer material, 1% to 2.5%; Conductive agent, 0.001% to 2.0%; Binder, 0.5%~2.5%.
14. The preparation method according to any one of claims 10 to 13, characterized in that: The monomer material includes a water-soluble monomer material; preferably, the water-soluble monomer material includes at least one of aniline and dopamine hydrochloride.
15. The preparation method according to any one of claims 10 to 14, characterized in that: Included steps Mixing the negative electrode active material and the conductive agent to obtain a mixed material; The mixed material is mixed with an aqueous solution of dopamine hydrochloride to prepare a composite negative electrode material; the composite negative electrode material comprises the negative electrode active material, a prefabricated film coated on the surface of the negative electrode active material particles and the conductive agent dispersed in the prefabricated film, and the material of the prefabricated film is polydopamine formed by polymerization reaction of dopamine hydrochloride; Mixing the composite negative electrode material with a binder to obtain a slurry; The slurry is used to form a negative electrode active material layer on a negative electrode current collector to obtain a negative electrode.
16. The preparation method according to claim 15, characterized in that: In the step of mixing the mixed material with an aqueous solution of dopamine hydrochloride to prepare a composite negative electrode material: a Tris buffer solution is also added to adjust the pH of the mixed material and the aqueous solution of dopamine hydrochloride.
17. The preparation method according to claim 16, characterized in that: In the step of mixing the mixed material with an aqueous solution of dopamine hydrochloride to prepare a composite negative electrode material, the control parameters include at least one of the following (1) to (3): (1) The mass concentration of dopamine hydrochloride is 3% to 8%; (2) The concentration of the Tris buffer solution is 0.05M to 0.15M; (3) The Tris buffer solution adjusts the pH of the mixture of the mixture and the aqueous solution of dopamine hydrochloride to 7.5-9.
18. A battery, characterized in that: A negative electrode comprising the negative electrode according to any one of claims 7 to 9, or a negative electrode prepared by the preparation method according to any one of claims 10 to 17.
19. An electrical equipment, characterized in that: A battery comprising the battery of claim 18.
Citation Information
Patent Citations
Method for prefabricating SEI film of lithium ion battery
CN110890516A
Double-layer coated silicon-based composite negative electrode material and preparation method thereof
CN111048769A
Battery positive and negative electrode active material and preparation method thereof
CN114678529A
Preparation method of silicon-coated carbon negative electrode material
CN118472210A
Binder, preparation method therefor, and use thereof
WO2023005520A1
Cited By
Negative pole piece, electrochemical device and preparation method of negative pole piece
CN120497280A